Influencia de la recaudación tributaria sobre los negocios agrícolas en Ecuador: Un análisis a nivel provincial - García Romero, Héctor Ismael (2024)
This article investigates the influence of tax collection on agricultural businesses in Ecuador at the provincial level. It initially hypothesizes a positive correlation between effective fiscal management and the growth of the agricultural sector. However, the findings do not reveal a significant statistical correlation between provincial tax collection and agricultural development. This challenges the assumption that fiscal policies alone can boost agricultural growth, underscoring the importance of considering other factors such as local public policies and agricultural associativity. The study suggests a more holistic approach, incorporating various factors beyond fiscal measures, for effective agricultural development. This conclusion opens new directions for future research aimed at understanding the complex dynamics of economic development in agriculture.